Shop different. - Berenstain, Adam.
Buying music has always involved tough decisions. Rolling Stones or Beatles? CD or LP? The mall or the indie record store with the cute cashier? These questions have plagued music fans for decades, but the iTunes Store changed everything. Thanks to its convenience, huge catalog, and iPod friendliness, iTunes now sells more music in the United States than any other retailer, either online or brick-and-mortar. But choices remain. iTunes megastore model, while others cater to customers with specific taste. Each sells high-quality MP3 files that play on Macs and iPods, but they supply them in different bit rates (a measure of data that helps determine sound quality) and from catalog of varying sizes. We've compared nine top iTunes competitors to see which most deserve your time and money. After all, freedom of choice is music to a Mac user's ears.
Keywords: Music; MP3 (Audio coding standard); Music stores; iTunes